2017
DOI: 10.1088/1361-665x/aa7710
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing power generation of floating wave power generators by utilization of nonlinear roll-pitch coupling

Abstract: We propose utilization of the nonlinear coupling between the roll and pitch motions of wave energy harvesting vessels to increase their power generation by orders of magnitude. Unlike linear vessels that exhibit unidirectional motion, our vessel undergoes both pitch and roll motions in response to frontal waves. This significantly magnifies the motion of the vessel and thus improves the power production by several orders of magnitude. The ocean waves result in roll and pitch motions of the vessel, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
(50 reference statements)
0
6
0
1
Order By: Relevance
“…This type of nonlinear Froude-Kylov force model has subsequently been used in [29][30][31][32][33][34] to investigate parametric resonance in WECs. Other nonlinear hydrodynamic modelling approaches include only modelling the restoring force nonlinearly, rather than the entire Froude-Krylov force [35][36][37][38][39][40]. Modelling parametric resonance has also been explored through high-fidelity CFD simulations [41].…”
Section: Parametric Resonance In Wecsmentioning
confidence: 99%
“…This type of nonlinear Froude-Kylov force model has subsequently been used in [29][30][31][32][33][34] to investigate parametric resonance in WECs. Other nonlinear hydrodynamic modelling approaches include only modelling the restoring force nonlinearly, rather than the entire Froude-Krylov force [35][36][37][38][39][40]. Modelling parametric resonance has also been explored through high-fidelity CFD simulations [41].…”
Section: Parametric Resonance In Wecsmentioning
confidence: 99%
“…Literature Review (Yerrapragada et al, 2017;Platzer and Sarigul-Klijn, 2018;Reis and Gallo, 2018;Goswami et al, 2019;Ranjbaran et al, 2019;Stiubiener et al, 2020;Hu et al, 2020;Li et al, 2020;Konur et al, 2020).…”
Section: Introductionunclassified
“…In this study, a small-scale autonomous hydrofoil boat construction is demonstrated for proposed technology testing. In an effort to increase efficiency in power generation by utilisation of nonlinear roll-pitch coupling on a ship, Yerrapragada et al (2017), used a small-scale ship to describe the advantages of this system in detail. Reis and Gallo (2018), described power production from waste heat by an organic Rankine cycle, aimed at increasing the thermal efficiency and minimising greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The idea behind parametrically excited systems is the use of large system responses near instabilities, e.g. see [6][7][8][9][10][11][12][13][14][15], among others. Within the huge range of nonlinear EH systems, there are some particular themes of note; natural single-potential nonlinearities (classical continuous nonlinear systems like the Van-der-Pol or Duffing oscillator, a pendulum, etc.…”
Section: Introductionmentioning
confidence: 99%